Open-Plan Office and Its Impact on Interpersonal Relationships - Alsarraj, Hadeal Alaa Taha (Auckland University of Technology, 2019)
In a modern industrialised world, many employees work in an open-plan office environment. Therefore, the effect of the open-plan office on interpersonal relationships and worker wellbeing is important to investigate. This study examines the lived experiences of employees who work in open-plan office environments. The academic literature illustrates how the open-plan office environment impacts on interpersonal relationships and worker wellbeing; suggesting that the open-plan office environment influences human behaviour and interaction. The positive aspects of open-plan office layouts are that they increase worker visibility, communication, collaboration, team cohesion and worker engagement. Other research outlines the negative impact of working in open-plan offices; factors such as noise, distraction and privacy issues. Seven people were interviewed for this study, participants were recruited from my personal and professional networks. Interviews were face to face and semi-structured in design. Interviews were transcribed, and the data was analysed through thematic analysis. Themes were generated during analysis to answer the research questions: 1. How does the open-plan office environment impact on employee interpersonal relationships? 2. What are the implications of open-plan office environments for employee wellbeing? Participants within this study generally felt positive about working in an open-plan office, and reported healthy working relationships. On the other hand, participants were often distracted by overhearing their co-workers talk and had preferences for a quieter environment. Through the findings, this research has provided insight into the interpersonal relationships and wellbeing of workers in open-plan office environments and recommendations for future research are provided.
Keywords: Open-plan; Interpersonal relationships; Office; Office design; Relationships; Office layout; Management; Wellbeing; Work station; Job statisfaction; Privacy; Organisational culture; Overhearing conversations; Supportive leadership